2021
DOI: 10.3390/s21186126
|View full text |Cite
|
Sign up to set email alerts
|

Camera Assisted Roadside Monitoring for Invasive Alien Plant Species Using Deep Learning

Abstract: Invasive alien plant species (IAPS) pose a threat to biodiversity as they propagate and outcompete natural vegetation. In this study, a system for monitoring IAPS on the roadside is presented. The system consists of a camera that acquires images at high speed mounted on a vehicle that follows the traffic. Images of seven IAPS (Cytisus scoparius, Heracleum, Lupinus polyphyllus, Pastinaca sativa, Reynoutria, Rosa rugosa, and Solidago) were collected on Danish motorways. Three deep convolutional neural networks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This option supports a more efficient identification of this invasive species and may facilitate timely intervention to avoid its spread in areas of interest. With the support of aerial imaging, tree composition can be mapped with high accuracy and monitored easily, quickly and more accurately in order to detect the changes of invasive tree species both spatially and temporally (da Silva et al., 2023; Dyrmann et al., 2021). This also provides a valuable practical option in the mapping of forest trees where there are stands mixed with invasive tree species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This option supports a more efficient identification of this invasive species and may facilitate timely intervention to avoid its spread in areas of interest. With the support of aerial imaging, tree composition can be mapped with high accuracy and monitored easily, quickly and more accurately in order to detect the changes of invasive tree species both spatially and temporally (da Silva et al., 2023; Dyrmann et al., 2021). This also provides a valuable practical option in the mapping of forest trees where there are stands mixed with invasive tree species.…”
Section: Discussionmentioning
confidence: 99%
“…Gathering stand‐level data, therefore, is important for implementing sustainable forest management practices in order to preserve biodiversity and multifunctional ecosystem services (Vo et al., 2013). Knowledge on the species composition is also important in quantifying timber volume and above ground biomass (Brahma et al., 2021; Nagy et al., 2020; Vo et al., 2013; Vorster et al., 2020), in nature conservation and landscape protection (Blackman, 2013; Zhang & Xie, 2012), and in tracking the spread of invasive tree species (Asner et al., 2008; Wilfong et al., 2009; Baron et al., 2018; Dyderski & Jagodziński, 2020; Dyderski & Pawlik, 2020; Dyrmann et al., 2021; Lake et al., 2022; da Silva et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pardo‐Primoy and Fagúndez (2019) used GSV to assess the distribution and recent spread of an invasive grass species in industrial sites in Galicia (Spain). Dyrmann et al (2021) also showed that mapping of invasive plants along roadsides is possible based on images taken from a driving vehicle, although they did not use GSV, but used their own equipment to obtain such images. An important limitation of the GSV system is that images are not always taken on the same date, or even the same season.…”
Section: Three Promising Avenues For the Use Of Photos In Ecological ...mentioning
confidence: 99%
“…This reduces the probability of plants being detected (e.g. for species that are less distinct when not flowering) and makes GSV less suitable for, for example, phenology studies (Dyrmann et al, 2021; Kotowska et al, 2021).…”
Section: Three Promising Avenues For the Use Of Photos In Ecological ...mentioning
confidence: 99%
See 1 more Smart Citation